Research on the Operation and Communication Strategies of League of Legends IP - A Case Study on the Launch of League of Legends: Wild Rift (China Server) - Li, Yiming (Transactions on Social Science, Education and Humanities Research, 2024)
League of Legends, as a renowned and influential IP in the gaming industry for more than a decade, has consistently dominated the MOBA market. With its engaging gameplay, vast roster of unique champions, and thriving esports scene, League of Legends has garnered a loyal and dedicated player base worldwide. However, recognizing the evolving gaming landscape, Riot Games, the creator of League of Legends, ventured into the mobile gaming realm, expanding their IP beyond the PC platform. One of the notable outcomes of this expansion is League of Legends: Wild Rift, popularly known as League of Legends Mobile. This mobile adaptation aims to bring the immersive League of Legends experience to a broader audience and tap into the growing demand for mobile gaming. This study will focus on the Chinese version of League of Legends Mobile. By conducting a comprehensive research and analysis, the study aims to identify potential issues by comparing League of Legends Mobile and Honor of kings and provide strategic recommendations for Riot Games to enhance the performance and competitiveness of League of Legends Mobile in the Chinese mobile MOBA market.